The Constituent Power in Islamic Constitutional Jurisprudence: A Comparative Study - Bouhazama مصطفى (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: Every time Muslim countries attempt to draft or amend their constitutions, the issue of the position of Islamic law in these constitutions is raised. Therefore, this article aims to study the peculiarities of the constituent power in Islamic constitutional jurisprudence and to highlight the possibility of Islamic constitutional jurisprudence benefiting from the gains of Western democracies in exercising the constituent power that sets or amends the constitution. Methods: The study follows a descriptive, analytical, and comparative methodology, in which the peculiarities of the constituent power in Islamic constitutional jurisprudence were reviewed, and the opinions of some Islamic constitutional jurists were analyzed regarding the source of the constitution and the method of its formulation. The study also included some comparisons between the peculiarities of the emergence of the concept of constituent power in Western constitutional experiences and its peculiarities after its transfer to Islamic countries. Results: The exercise of constituent power in Islamic countries must take place within the framework of Islamic law, with the possibility of benefiting from the gains of Western democracies in a manner that does not conflict with Islamic principles and morals in governance. Conclusions: More openness to the Western foundational experiences and the gains they have achieved in exercising the constituent power, especially those that do not contradict the principles of Islam. It is also deepening research in Islamic constitutional jurisprudence related to constituent power.